Organization of the Catecholaminergic System in the Short-Lived Fish Nothobranchius furzeri - Borgonovo, Janina; Ahumada-Galleguillos, Patricio; Oñate-Ponce, Alejandro; Allende-Castro, Camilo; Henny, Pablo; Concha, Miguel L. (Frontiers in Neuroanatomy, 2021)
The catecholaminergic system has received much attention based on its regulatory role in a wide range of brain functions and its relevance in aging and neurodegenerative diseases. In the present study, we analyzed the neuroanatomical distribution of catecholaminergic neurons based on tyrosine hydroxylase (TH) immunoreactivity in the brain of adult Nothobranchius furzeri. In the telencephalon, numerous TH+ neurons were observed in the olfactory bulbs and the ventral telencephalic area, arranged as strips extending through the rostrocaudal axis. We found the largest TH+ groups in the diencephalon at the preoptic region level, the ventral thalamus, the pretectal region, the posterior tuberculum, and the caudal hypothalamus. In the dorsal mesencephalic tegmentum, we identified a particular catecholaminergic group. The rostral rhombencephalon housed TH+ cells in the locus coeruleus and the medulla oblongata, distributing in a region dorsal to the inferior reticular formation, the vagal lobe, and the area postrema. Finally, scattered TH+ neurons were present in the ventral spinal cord and the retina. From a comparative perspective, the overall organization of catecholaminergic neurons is consistent with the general pattern reported for other teleosts. However, Nothobranchius furzeri shows some particular features, including the presence of catecholaminergic cells in the midbrain. This work provides a detailed neuroanatomical map of the catecholaminergic system of Nothobranchius furzeri, a powerful aging model, also contributing to the phylogenetic understanding of one of the most ancient neurochemical systems.